Antioxidants as Molecular Probes: Structurally Novel Dihydro-m-Terphenyls as Turn-On Fluorescence Chemodosimeters for Biologically Relevant Oxidants - Víctor González-Ruiz; Jegathalaprathaban Rajesh; Ana I. Olives; Damiano Rocchi; Jorge Gómez-Carpintero; Juan F. González; Vellaisamy Sridharan; M. Antonia Martín; J. Carlos Menéndez (MDPI AG, 2020)
One interesting aspect of antioxidant organic molecules is their use as probes for the detection and quantitation of biologically relevant reactive oxidant species (ROS). In this context, a small library of dihydroterphenyl derivatives has been synthesised and studied as fluorescent chemodosimeters for detecting reactive oxygen species and hypochlorite. The fluorescence quantum yields of these molecules are negligible, while the corresponding aromatized compounds formed upon oxidation show moderate to high native fluorescence, depending on their structures. The fluorescence signal is quickly developed in the presence of trace amounts of the probe and the analytes in acetonitrile media at room temperature, with good analytical figures. ROS detection in aqueous media required incubation at 37 °C in the presence of horseradish peroxidase, and was applied to glucose quantitation by coupling glucose oxidation by O2 to fluorescence detection of H2O2. The mild reaction conditions and sensitive fluorescent response lead us to propose dihydroterphenyls with an embedded anthranilate moiety as chemosensors/chemodosimeters for ROS detection.